Study on Recrystallization Process of Poly(DL-lactide)/Poly(ethylene glycol) Diblock Copolymer - Chen Xiaoqi; Bai Lu; Li Chengyu; Tian Jia; Zhou Haijun; Zhou Mengmeng; Xiao Jijun; Li Yantao (MATEC Web of Conferences, 2022)
Poly (DL-lactide)/Poly (ethylene glycol) diblock copolymer is successfully synthesized with mPEG and DL-LA as main raw materials, and the residual monomers of the polymer were removed by recrystallization. FT-IR is used to characterize the structure of the polymer. Gas chromatography is used to determine the residual monomers and residual solvent of the polymer. The solubility of polymer in different solvents was determined, and the effect of different solvent systems on the removal of residual monomers in copolymer were discussed. The results showed that the Poly(DL-lactide)/Poly(ethylene glycol) diblock copolymer was recrystallized with acetone/ isopropyl ether solvent system has the best ability to remove residual monomers, and the residual monomers of the obtained polymer are less than 0.01 wt%, the total residual solvent is only 0.24 wt%, and the productivity is as high as 95.5 wt%.